Educação Especial na Produção Acadêmica do PPGED/UFU: das contradições às proposições - Nazari, Ana Clara Gomes (2019)
This study, linked to the research line Pedagogical Knowledge and Practices of the Program of Post Graduation in Education of the Federal University of Uberlândia (PPGED / UFU), has as its guiding question to analyze the contributions of research already produced and with the intention of breaking with the vision of a purely descriptive analysis we draw the problematic that guides the investigation: With respect to the theoretical and methodological presuppositions, which contradictions and propositions can be identified in the production of the knowledge about Special Education, produced in the dissertations and theses defended in the Program of Post Graduation in Education of the Federal University of Uberlândia (PPGED / UFU), from 2007 to 2017? Starting from this problematic, we established as general objective: to analyze the contradictions and propositions in the production of knowledge in the researches on Special Education, produced in the dissertations and theses defended in the Program of Post Graduation in Education of the Federal University of Uberlândia (PPGED / UFU), in the period of 2007 to 2017. More specifically we aim to: catalog and analyze the dissertations and theses on Special Education defended in the PPGED / UFU in the period from 2007 to 2017; identifying its main objectives and presented results, as well as its theoretical and methodological bases; to understand the concept of Special Education established in these studies; to map the themes and types of deficiencies addressed, as well as their summaries, results and contributions; to contribute to the intensification of the debates that have the academic production in Special Education as object of study. In order to respond to these objectives, in our methodology we chose to base our work in a qualitative perspective. In addition, we classify our research as a bibliographical study, of epistemological character. Among the instruments used for the construction of the data of our investigation are: the analysis sheet. For the interpretation of the data we use Content Analysis. A total of 22 productions were analyzed, being 15 dissertations and 07 theses. Our reflections were organized in thematic axes, being these: the characterization of the research; the concept of Special Education involved; the theoretical and methodological bases of the research developed in the PPGED / UFU that have as a theme Special Education; mapping of the themes and type of disability addressed in these surveys; syntheses, results and contributions of these studies. Among the main results we find that the inclusion of people with disabilities in school (whether in basic or university education) permeates the discussions, sometimes dealing with specific issues, how this process is constituted within the school / university, other times suggesting ways that facilitate social interaction and school development of the subjects involved. We can add that the analyzed studies (mostly) enabled the discussion of the knowledge and practices necessary to mediate the teaching-learning process in Special Education in order to promote the insertion of this public in the different contexts, re-signifying their social relations and their identity formation, rethinking the practices of inclusion. From the point of view of the topic, we believe that our analyzes have a significant scientific relevance, while our study throws light on this area of Special Education and places it as a fertile field of discussions, reflections and actions, insofar as it highlights important aspects of academic production.